2014
DOI: 10.1186/1470-7330-14-10
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced [18 F] fluorodeoxyglucose-positron emission tomography/computed tomography in clinical oncology: tumor-, site-, and question-based comparison with standard positron emission tomography/computed tomography

Abstract: Background The present study aimed to evaluate the added value of contrast-enhanced computed tomography (ceCT) in comparison to standard, non-enhanced CT in the context of a combined positron emission tomography (PET)/CT examination by means of a tumor-, site-, and clinical question-based approach. Methods Analysis was performed in 202 patients undergoing PET/CT consisting of a multiphase CT protocol followed by a whole-body PET. The Cochran Q test was performed, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In this context, as CT might be more to detect smaller lesions, also ones within the liver, hybrid imaging with FDG PET and full diagnostic contrast-enhanced CT has been proposed and might be of use in selected cases. 59 However, it has to be underlined that MRI has been demonstrated to be superior to both CT and FDG PET for the detection of small liver lesions with the use of hepatic-specific MR contrast agents. 60 …”
Section: Restaging In Inconclusive Cases and Metastatic Patients Who mentioning
confidence: 99%
“…In this context, as CT might be more to detect smaller lesions, also ones within the liver, hybrid imaging with FDG PET and full diagnostic contrast-enhanced CT has been proposed and might be of use in selected cases. 59 However, it has to be underlined that MRI has been demonstrated to be superior to both CT and FDG PET for the detection of small liver lesions with the use of hepatic-specific MR contrast agents. 60 …”
Section: Restaging In Inconclusive Cases and Metastatic Patients Who mentioning
confidence: 99%
“…Fourth and last, contrast-enhanced PET/CT in this study was performed in singlephase manner, so our results may not be generalizable to multi-phase contrast-enhanced PET/CT, which was previously suggested by some authors. (17) In contrast to other reports that studied in specific types of cancer, the strengths of this study are its prospective design and the fact that we studied different types of cancer, which increases the generalizability of our findings. However, further investigation in those cancers with a small number of cases, as well as in other indications, is needed to confirm the results of this study.…”
Section: Discussionmentioning
confidence: 88%
“…Actually, SUV could be underestimated in malignant pleural effusion with small cell component, small pulmonary nodule, or ground-glass lesion [31,32]. Three falsenegative cases of this study were also pleural and pulmonary metastasis, which could be found in follow-up chest CT. Additional contrast-enhanced CT (ceCT) may also serve as a complementary tool by discerning vessel or bowel activity [33]. However, the increased cost and radiation exposure can outweigh the perceived benefit.…”
Section: Discussionmentioning
confidence: 99%